2015
DOI: 10.15406/jpcpy.2015.03.00132
|View full text |Cite
|
Sign up to set email alerts
|

Is Mental Health a Burning Health Issue for Indian Elderly?

Abstract: One of the important public health issues worldwide is the rise of higher proportion of older aged with advancement of medicine, prolonged life expectancy and for improved health care facilities. Demographic projections suggest that mental illness along with heart diseases, AIDS and cancer will account for the top four illnesses around the globe very soon. It ranks up at the top along with heart disease, cancer, obesity, AIDS and injuries as leading causes of suffering. Increased longevity of elderly led to hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…The current study also showed a significant association between MDs and being unmarried, low economic status, current smoking; the findings that agree with many other studies. 26,38,44,45…”
Section: Discussionmentioning
confidence: 99%
“…The current study also showed a significant association between MDs and being unmarried, low economic status, current smoking; the findings that agree with many other studies. 26,38,44,45…”
Section: Discussionmentioning
confidence: 99%